Economic Effects of Foreign Direct Investment on the Sakhalin Region from 1995 to 2005 - Suganuma, Keiko (Center for Far Eastern Studies University of Toyama, 2011)
application/pdf This paper quantitatively evaluates the economic effects of foreign direct investment (FDI) on Russia’s regional development, concentrating on the Sakhalin region in the construction stage of both Sakhalin Projects 1 and 2. The region has enjoyed a relatively large amount of FDI compared to others with similar situations of relevant early main economic elements. This analysis shows that the FDI into the region has had a positive economic effect on the nominal wage levels, domestic investment, international trade, economic growth, and the upgrading and expanding of social capital. On the other hand, the effects on employment, real wage levels, technology, and budget revenue are not statistically significant. Article Far eastern studies : FES, vol.10, Page 1-23 journal article